Analytical fatigue life formulation for notches informed by crystal plasticity - Ashraf, Farhan; Cini, Andrea; Castelluccio, Gustavo M. (Elsevier, 2022)
Damage from small manufacturing defects often go unnoticed until fatigue cracks have grown beyond repairability. These cracks initiate at defects with dimensions on par with the microstructure length scale (e.g., 5–200 µm deep), which affects fatigue variability and renders most engineering prognosis methods inapplicable. This work develops a novel microstructure-sensitive formulation that reduces computational efforts by decoupling geometric and microstructural contributions to fatigue cracking. Crystal plasticity finite element models with and without geometry induced strain gradients were considered to assess the role of defects independently from the microstructure. The analysis results in a fatigue life analytical formulation whose parameters depend on the microstructure and defect morphology.
Keywords: Small cracks; Crystal plasticity; Microstructure; Scribe marks; Micromechanical notches